Q. 94.8( 5 Votes )

Find , when

x = a(cosθ + θ sinθ) and y = a(sinθ – cosθ)

Answer :

the given equation are x = a(cosθ + θ sinθ)


And y = a(sinθ – cosθ) so,

= a

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses